Prognostic analysis of patients with operable gastric cancer and tolerability to adjuvant radiochemotherapy - DANE, FAYSAL (AEPRESS SRO, 2012)
The aim of this study is to evaluate the tolerability and toxicity of adjuvant chemoradiotherapy (CRT) and to analyze the prognosis in patients with operable gastric cancer. The retrospective analysis included 723 patients with operable gastric cancer; stage IB-IV (M0), received adjuvant CRT from 8 Medical Centers in Turkey between 2003 and 2010. The patients' age, sex, tumor localization, Lauren classification, grade and stage of the disease, type of dissection, the toxicity and tolerability status and survival rate were analyzed. All patients were divided into two groups as tolerable group to adjuvant CRT and intolerable group to adjuvant CRT. Among the patient, 73.9% had stage III-IVM0 disease; 61.0% had the intestinal type of gastric cancer, 51.1% had the distal type, and 61.4% had undergone D2 dissections. The number of patients who completed the entire course of the adjuvant CRT was 545 (75.4%). The median follow-up period was 20.8 months (range: 1.5-107 months). Overall Survival (OS) rates were 80% and 52%, while the relapse free survival (RFS) rates were 75% and 48% at 1 and 3 years, respectively. In the univariate analysis of the groups based on the the age defined as <65 or >= 65 (p=0.16 / p=0.003), Lauren classification (p=0.004 / p<0.001), localization of tumor (p=0.02 / p=0.04), tumor grade (p=0.06 / p=0.003), disease stage (p<0.001 / p<0.001), type of dissection (p=0.445 / p=0.043), presence or absence of toxicity (p=0.062 / p=0.077) and tolerability of the therapy (p=0.002 / p=0.001). In the cox regression analysis, tumor stage (Hazard Ratio (HR): 0.332; 95% confidence interval (CI): 0.195-0.566; p<0.001), and tolerability (HR: 0.516; 95% CI: 0.305-0.872; p=0.014), were found to be related with the OS. Tumor stage (HR: 0.318; 95% CI: 0.190-0.533; p=<0.001) and tolerability (HR: 0.604; 95% CI: 0.367-0.995; p=0.048) were observed to be statistically significant in terms of the RFS. We have observed that whether a patient can or cannot tolerate adjuvant CRT due to its toxicity is an independent prognostic factor besides the known prognostic factors like tumor stage and Lauren classification. We are of the opinion that the treatment of patients who cannot tolerate adjuvant CRT should be replaced with less toxic adjuvant therapies.
Keywords: gastric cancer; prognosis; tolerability; SURVIVAL; STOMACH